Thyroid Hormone-dependent Epigenetic Suppression of Herpes Simplex Virus-1 Gene Expression and Viral Replication in Differentiated Neuroendocrine Cells - Figliozzi, Robert W. (J Neurol Sci, 2014)
A global HSV-1 gene repression occurs during latency in sensory neurons where most viral gene transcriptions are suppressed. The molecular mechanisms of gene silencing and how stress factors trigger the reactivation are not well understood. Thyroid hormones are known to be altered due to stress, and with its nuclear receptor impart transcriptional repression or activation depending upon the hormone level. Therefore we hypothesized that triiodothyronine (T(3)) treatment of infected differentiated neuron like cells would reduce the ability of HSV-1 to produce viral progeny compared to untreated infected cells. Previously we identified putative thyroid hormone receptor elements (TREs) within the promoter regions of HSV-1 thymidine kinase (TK) and other key genes. Searching for a human cell line that can model neuronal HSV-1 infection, we performed HSV-1 infection experiments on differentiated human neuroendocrine cells, LNCaP. Upon androgen deprivation these cells undergo complete differentiation and exhibit neuronal-like morphology and physiology. These cells were readily infected by our HSV-1 recombinant virus, expressing GFP and maintaining many processes iconic of dendritic morphology. Our results demonstrated that differentiated LNCaP cells produced suppressive effects on HSV-1 gene expression and replication compared to its undifferentiated counterpart and T(3) treatment have further decreased the viral plaque counts compared to untreated cells. Upon washout of the T(3) viral plaque counts were restored, indicating an increase of viral replication. The qRT-PCR experiments using primers for TK showed reduced expression under T(3) treatment. ChIP assays using a panel of antibodies for H3 lysine 9 epigenetic marks showed increased repressive marks on the promoter regions of TK. In conclusion we have demonstrated a T(3) mediated quiescent infection in differentiated LNCaP cells that has potential to mimic latent infection. In this HSV-1 infection model thyroid hormone treatment caused decreased viral replication, repressed TK expression and increased repressive histone tail marks on the TK promoter.